A heterogeneous lattice structure modeling technique supported by multiquadric radial basis function networks. Issue 1 (30th December 2021) - Liu, Yuan; Yang, Huiyuan; Zhao, Yaoyao Fiona; Zheng, Guolei
ABSTRACT: With the rapid advancement of the multimaterial additive manufacturing (AM) technology, the heterogeneous lattice structures (HLSs) comprising the multiphase materials with gradual variations have become feasible and accessible to the industry. However, the multimaterial AM capabilities have far outpaced the modeling capability of design systems to model and thus design novel HLSs. To further expand the design space for the utilization of AM technology, this paper proposes a method for modeling HLS with complex geometries and smooth material transitions. The geometric modeling and material modeling problems are formulated in a rigorous and computationally effective manner. The geometric complexity of HLS is significantly reduced by a semi-analytical unit cell decomposition strategy that is applied to split HLS into material units: struts and connectors. The smooth material transitions of the connector associated with multimaterial struts are realized by interpolating the discrete material property values defined at control points using a multiquadric radial basis function network. Graphical Abstract: